PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V SD NEGERI 175786 SIAMBATON KEC PAKKAT - Hasibuan, Nove Silvia; Imelda Sihombing; Paska Sriulina Tarigan; Patri Janson Silaban; Heka Maya Sari Br Sembiring (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is a crucial aspect that must be continuously improved to achieve national goals and the advancement of knowledge. Therefore, teacher professionalism also needs to be enhanced in order to produce intelligent and creative students. One effort that can be made is by implementing creative learning models that are appropriate to the learning materials and students’ needs. This study was motivated by the low learning outcomes of fifth-grade students at SD Negeri 175786 Siambaton, as indicated by their daily test scores. This research employed a quantitative approach using a one-group pretest–posttest design. To identify students’ initial abilities, a pretest was administered, resulting in an average score of 62.67. The results showed that the implementation of the Creative Problem Solving learning model had an effect on the learning outcomes of fifth-grade students at SD Negeri 175786 Siambaton and was categorized as good, with an average posttest score of 78.0. The correlation test results indicated a correlation coefficient of 0.692, meaning that rcalculated (0.692) > rtable ​ (0.361); therefore, the alternative hypothesis (Ha) was accepted. Furthermore, the t-test results showed that tcalculated ​ > ttable ​, namely 5.707 > 1.697. Thus, it can be concluded that there is a positive and significant effect of the Creative Problem Solving learning model on Mathematics learning outcomes of fifth-grade students at SD Negeri 175786 Siambaton in the 2024/2025 academic year.